2007
DOI: 10.1161/01.str.0000254594.33408.b1
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Symptoms in Type A Aortic Dissections

Abstract: Background and Purpose-Aortic dissection typically presents with severe chest or back pain. Neurological symptoms may occur because of occlusion of supplying vessels or general hypotension. Especially in pain-free dissections diagnosis can be difficult and delayed. The purpose of this study is to analyze the association between type A aortic dissection and neurological symptoms. Methods-Clinical records of 102 consecutive patients with aortic dissection (63% male, median age 58 years) over 7.5 years were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
252
3
28

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(296 citation statements)
references
References 23 publications
13
252
3
28
Order By: Relevance
“…High-risk conditions and historical features (see Table 8). 59,[75][76][77] 72 Age >50 y 3 criteria are present (sensitivity >90%; specificity >90%) Recent-onset localized headache Temporary artery tenderness or pulse attenuation Elevated erythrocyte sedimentation >50 mm/h Arterial biopsy shows necrotizing vasculitis Behçet disease 73 Oral ulceration Oral ulceration plus 2 of the other 3 criteria Recurrent genital ulceration Uveitis or retinal vasculits Skin lesions-erythema nodosum, pseudo-folliculitis, or pathergy Ankylosing spondylitis 74 Onset of pain <40 83 …”
Section: Recommendations For Estimation Of Pretest Risk Of Thoracic Amentioning
confidence: 99%
“…High-risk conditions and historical features (see Table 8). 59,[75][76][77] 72 Age >50 y 3 criteria are present (sensitivity >90%; specificity >90%) Recent-onset localized headache Temporary artery tenderness or pulse attenuation Elevated erythrocyte sedimentation >50 mm/h Arterial biopsy shows necrotizing vasculitis Behçet disease 73 Oral ulceration Oral ulceration plus 2 of the other 3 criteria Recurrent genital ulceration Uveitis or retinal vasculits Skin lesions-erythema nodosum, pseudo-folliculitis, or pathergy Ankylosing spondylitis 74 Onset of pain <40 83 …”
Section: Recommendations For Estimation Of Pretest Risk Of Thoracic Amentioning
confidence: 99%
“…Gaul et al reported that chest pain was apparent in 94% of 72 AAAD patients without neurological symptoms but was only apparent in two thirds of 30 patients with symptoms. 5) Similarly in Japan, Imamura et al found that 16 of 98 patients (17%) had no pain. 6) The painless group more frequently had consciousness disturbance or other neurological symptoms and had more unfavorable outcomes.…”
mentioning
confidence: 94%
“…6 This temporal evolution of clinical and imaging findings strongly supported a direct correlation between AD and spinal cord ischemia in accordance with recent literature data. 1,2,4 Other possible etiologies of acute myelopathy (compression, infection, inflammation) were excluded by the emergently performed laboratory examinations and finally autopsy-verified extensive AD.…”
Section: Commentmentioning
confidence: 99%